Subject-related communicative language competence: Exploring future information technology specialists' learning and teaching - Kaldarova, Aissulu; Kulgildinova, Tulebike; Berdenova, Saule; Zakirova, Gulnara; Zhanabayeva, Svetlana (Journal of Education and e-Learning Research, 2024)
The need for IT professionals with fluency in foreign languages becomes increasingly critical as the Kazakhstani government implements steps to foster IT innovation. However, there are structural, geographical and professional imbalances in the interaction of supply and demand for IT professionals who can speak a foreign language in the modern labour market which is the main problem that is currently hindering the growth of the IT sector in Kazakhstan. The aim of this study was to assess the development of subject communicative language competencies (a) in linguistic or grammatical ability and (b) in discourse ability in first-year students for the proposed author's innovative learning technique in the educational process as well as the appropriate technological and systematic procedures. A mixed-research method was used in this study. The study involved 365 learners in the "Informatics" direction at the International University of Information Technologies in Almaty, Kazakhstan during the school year 2021-2022. According to the findings, the experiment participants did not develop subject-related communicative language competencies. The results show that the degree of capability formation is not satisfactory. 52.8% is the basic level, 41.6% is the production point and only 5.8% is the high level. Positive dynamics shaping learners' subject-related language communication competencies were identified as a result of the implementation of innovative techniques. This paper contributes to the research on teaching IT students in developing countries and highlights the most important factors that contribute to improve the level of subject-related communicative language competencies of IT students.